Treatment of Cyclosporin A retains host defense against invasive pulmonary aspergillosis in a non-immunosuppressive murine model by preserving the myeloid cell population. Issue 8 (17th November 2017) - Wong, Sarah Sze Wah; Rasid, Orhan; Laskaris, Paris; Fekkar, Arnaud; Cavaillon, Jean-Marc; Steinbach, William J.; Ibrahim-Granet, Oumaima
ABSTRACT: Cyclosporin A (CsA) is widely used as an immunosuppressive agent for organ transplant recipients. CsA inhibits calcineurin, which is highly conserved in mammals and fungi, and thus affects both types of organism. In mammals, the immunosuppressive effect of CsA is via hampering T cell activation. In fungi, the growth inhibitory effect of CsA is via interference with hyphal growth. The aim of this study was to determine whether CsA renders mice susceptible to invasive pulmonary aspergillosis (IPA) and whether it can protect immunosuppressed mice from infection. We therefore examined both the antifungal and the immunosuppressive activity of CsA in immunosuppressed and in immunocompetent mice infected with Aspergillus fumigatus to model IPA. We found that daily injections of CsA could not produce an antifungal effect sufficient to rescue immunosuppressed mice from lethal IPA. However, a 100% survival rate was obtained in non-immunosuppressed mice receiving daily CsA, indicating that CsA did not render the mice vulnerable to IPA. The lymphocyte subset was significantly suppressed by CsA, while the myeloid subset was not. Therefore, we speculate that CsA does not impair the host defense against IPA since the myeloid cells are preserved.